PELESTARIAN DAN KOMERSIALISASI PURA TIRTA EMPUL, DESA MANUKAYA, KABUPATEN GIANYAR: KAJIAN KOMUNIKASI MASSA - Made Novita Dwi Lestari (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
The debate between the goals of preservation and economic empowerment in cultural tourism with all its manifestations is still a heated debate among tourism experts and tourism businesses. While Bali tourism development from time to time, has undergone many changes along with the social dynamics that exist in Balinese society . This article uses a review of the literature that deals with the problem being solved, through a study of scientific journals, opinions, and online articles, then compares and finds similarities and differences so that they can be used to explain the problem that is to be solved. dualism that needs to be integrated to realize a balance between the goals of cultural preservation and economic development for Bali is specifically studied in the approach of mass communication. So that in this case, people must be wiser in using mass media to bring our culture to the right future.Keywords: Preservation, Commercialization, Culture, Mass Communication